2010
DOI: 10.1016/j.ahj.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Trends in echocardiography utilization in the Veterans Administration Healthcare System

Abstract: Background There is growing concern over the impact of accelerating use of diagnostic imaging services on health care spending. Echocardiography is an important cardiovascular imaging procedure, but little is known about trends in its use or utilization. We examine trends in the utilization of echocardiography in a national health care system. Methods We used administrative data from the Veterans Healthcare Administration (VA) from 2000 to 2007 to identify patients receiving regular medical care (VA users) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Previous studies have shown minimal growth in the rate of repeat echocardiography but were limited to evaluating only the number of repeat studies within the same calendar year. (5,23) In our study, in which a repeat echocardiogram was defined as having occurred within 365 days of a prior outpatient procedure, repeat testing increased by an average of 10% per year.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous studies have shown minimal growth in the rate of repeat echocardiography but were limited to evaluating only the number of repeat studies within the same calendar year. (5,23) In our study, in which a repeat echocardiogram was defined as having occurred within 365 days of a prior outpatient procedure, repeat testing increased by an average of 10% per year.…”
Section: Discussionmentioning
confidence: 76%
“…The authors of that study hypothesized that Veterans Administration policy changes to increase the number of veterans eligible for services without an immediate increase in procedural capacity may have resulted in stabilization of echocardiography rates. (23) There were no such policy changes in Ontario during the study period we examined. In our study, physicians appeared to be increasingly reliant on echocardiography to clinically manage patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, we did not prevent any provider from ordering a study, even if it clearly would not have been indicated under the AUC or prompt scenarios. Alternatively, the increase in TTE ordering in more recent months may be due to the continued increase in the veteran population cared for at our institution, as previous analysis has shown much of the change in TTE ordering with the VA system over a several-year period was due to an increased number of patients rather than per-patient use 18. In fact, our small reduction in TTE ordering may have been larger if the veteran population for which DVAMC is responsible and the number of visits associated with that population had remained flat.…”
Section: Discussionmentioning
confidence: 99%
“…7 Our work confirms that growth of this modality remains steady and contrasts strikingly with the stability of echocardiography rates in the relatively fixed budget VA health care system: from 2000 -2007, the rate of echocardiography in the VA grew only 4%. 8 It is equally important to highlight that rates of some procedures, notably percutaneous coronary interventions (PCI), grew very modestly. From 1993-2001, PCI rates more than doubled in US Medicare beneficiaries 5 and nearly tripled in Ontario from 1992-2001.…”
Section: Andrus and Welch Growth Of Medicare Services By Cardiologistmentioning
confidence: 99%